Knowledge of Cervical Cancer and Screening Practices among Women in Bindura District, Mashonaland Central Province, Zimbabwe - Chipfuwa, Tirivanhu; Mangwanda, Urita (KHD-Production, 2024)
Cervical cancer (CaCx) is the most common cancer among women and is also the major cause of death worldwide. It is the most common cancer among black Zimbabwean women accounting for 29.4% of the cases. The purpose of this study was to determine the knowledge of cervical cancer and screening practices among women in Bindura District, Zimbabwe. A descriptive cross–sectional research study was conducted. The study sample consisted of 100 consenting women who were selected from Bindura Hospital, Chipadze and Chiwaridzo Council Clinics using simple random sampling method. Data were collected by face-to-face interviews using a questionnaire as a guide. Data were processed using Statistical Package Social Sciences (SSPS) software version 20 and analyzed descriptively. Data revealed that knowledge of risks factors and preventive measures for cervical cancer was poor as only (31%) had high knowledge levels. Although the majority of the respondents (77%) had heard about cervical cancer screening only (22%) were screened, the major reason cited being lack of knowledge. Perception of risk for cervical cancer was poor as (58%) of the respondents did not perceive to be at risk of cervical cancer. The study revealed that cervical cancer knowledge level was very low and screening practices were very poor. Therefore, health care providers need to intensify awareness on cervical cancer through health education across women of all age groups. The government should also make cervical cancer screening available and accessible at most health care facilities.